MODEL PEMBELAJARAN LANGSUNG BERBASIS PERMAINAN MONOPOLI MODIFIKASI TERHADAP KEMAMPUAN MENGENAL NILAI UANG BAGI ANAK AUTISM - Ayu Elandini, Senja (Jurnal Pendidikan Khusus, 2017)
ABSTRACT This research purpose was to observe whether there was influence of using direct learning model based modification monopoly game toward recognizing money value ability to autism children in SDN Sambikerep 1 Surabaya or not. This research used pre experiment kind with one group pre test – post test design.From the research result it was then analyzed using sign test formula. It was obtained that Zh value = 2,05 > Zt = 1,96 to significant level 5%. So, it could be concluded that there was influence of direct learning model based modification monopoly game toward recognizing money value ability to autism children in SDN Sambikerep 1 Surabaya.   Keywords: Direct learning model, modification monopoly game, money value.